2021
DOI: 10.1038/s41438-021-00510-5
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-specific signatures of metabolites and proteins in asparagus roots and exudates

Abstract: Comprehensive untargeted and targeted analysis of root exudate composition has advanced our understanding of rhizosphere processes. However, little is known about exudate spatial distribution and regulation. We studied the specific metabolite signatures of asparagus root exudates, root outer (epidermis and exodermis), and root inner tissues (cortex and vasculature). The greatest differences were found between exudates and root tissues. In total, 263 non-redundant metabolites were identified as significantly di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 65 publications
0
13
0
Order By: Relevance
“…This differentiation of the profiles in flavonoids (more abundant in green) and saponins (more abundant in white spears) might have been anticipated since previous studies have reported generally high flavonoid contents in photosynthetic tissues [ 40 ], and high saponin levels in plant parts growing below-ground [ 18 , 38 ]. Using a complementary approach, Yi et al, (2019) performed de novo transcriptome sequencing in both green and white types of a commercial variety (Atlas) and found significant differences between the two asparagus types in that 21% of the genes involved in the biosynthesis of the flavonoid rutin were upregulated in green and 4% of the genes involved in the biosynthesis of the saponin protodioscin were upregulated in white asparagus [ 41 ].…”
Section: Discussionmentioning
confidence: 82%
“…This differentiation of the profiles in flavonoids (more abundant in green) and saponins (more abundant in white spears) might have been anticipated since previous studies have reported generally high flavonoid contents in photosynthetic tissues [ 40 ], and high saponin levels in plant parts growing below-ground [ 18 , 38 ]. Using a complementary approach, Yi et al, (2019) performed de novo transcriptome sequencing in both green and white types of a commercial variety (Atlas) and found significant differences between the two asparagus types in that 21% of the genes involved in the biosynthesis of the flavonoid rutin were upregulated in green and 4% of the genes involved in the biosynthesis of the saponin protodioscin were upregulated in white asparagus [ 41 ].…”
Section: Discussionmentioning
confidence: 82%
“…Asparagus ( Asparagus officinalis L.) belongs to the lily family, is a perennial and diecious vegetable popularly consumed worldwide. Asparagus contains a high level of nutrients and antioxidant compounds, and has positive effects on preventing hypertension, heart disease and certain cancers [ 27 , 28 , 29 ]. Asparagus originate in the Mediterranean region andis now cultivatedin many countries worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Using leaf and stem segments, different metabolites of each species were identified depending on the analyzed organ segment, and it was concluded that the elaboration of metabolomic profiles is a useful tool aiding the rapid characterization of metabolites in plants and, thus, revealing their chemodiversity (diversity of phytochemicals delimited according to botanical taxa and/or tissues or specific phenological states) (Lee et al 2020 ; Müller et al 2020 ; Saito 2020 ). Similarly, there are many valuable studies in which high-performance metabolomic tools are used to investigate the metabolic diversity to evaluate plant diversity (Döll et al 2021 ; Marr et al 2021 ). However, most of these studies adopt the analysis of chemodiversity as a useful approach solely for comparisons between different conditions (experimental variables), without truly evaluating diversity and/or structural patterns based on a strict census of the phytochemical compounds that make up the metabolome per se (Shi et al 2020 ; Zhao et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%